22 Simulation-based training in paediatric anaesthesia: the experience of running a managing emergencies in paediatric anaesthesia (MEPA) programme at one institution. (22nd November 2019) - Beer, David de; Smith, Jonathan; Walsh, Bill
Abstract : The Managing Emergencies in Paediatric Anaesthesia (MEPA) simulation course was established over a decade ago to provide anaesthetic trainees the opportunity to develop and practice management strategies for anaesthetic emergencies in children. 1 Central to the success of MEPA has been its collaborative nature, with consultant paediatric anaesthetists nationally reaching consensus regarding content, structure and educational goals. Within this framework, a number of evidence-based, peer-reviewed scenarios were developed for emergencies considered key competencies for any anaesthetist providing care to children. MEPA has subsequently expanded across 5 continents and evolved to include a course for non-specialist consultants based on the RCoA matrix for revalidation. 2 MEPA for trainees was launched at Great Ormond Street Hospital in 2008 with the consultant course being introduced in 2010. With five trainee and five consultant courses currently being run each year in the Clinical Simulation Centre, we remain the largest provider of MEPA training nationally. Feedback has been consistently excellent with 96% of candidates reporting a positive impact on clinical care and patient safety, and over half stating that they had learnt something not taught on any other course. 3 Another important goal of MEPA is content dissemination and GOSH has run workshops nationally and internationally and established programs in South Africa and Kenya. The latter was particularly influential as a train-the-trainer programme for senior clinicians from six African countries was conducted to equip providers to run the courses independently. References: Molyneux M, Lauder G. A national collaborative simulation project: paediatric anaesthetic emergencies. Pediatr Anesth 2006;16: 1302. Everett TC, MacKinnon R, de Beer D, et al. Ten years of simulation-based training in pediatric anesthesia: The inception, evolution, and dissemination of the Managing Emergencies in Pediatric Anesthesia (MEPA) course. Paediatric Anaesthesia 2017; 27: 984-990. J Thomson, de Beer D. MEPA feedback report. Personal communication.